2022
DOI: 10.1302/0301-620x.104b9.bjj-2022-0116.r1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating incidence rates of periprosthetic joint infection after hip and knee arthroplasty for osteoarthritis using linked registry and administrative health data

Abstract: Aims The aim of this study was to estimate the 90-day periprosthetic joint infection (PJI) rates following total knee arthroplasty (TKA) and total hip arthroplasty (THA) for osteoarthritis (OA). Methods This was a data linkage study using the New South Wales (NSW) Admitted Patient Data Collection (APDC) and the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR), which collect data from all public and private hospitals in NSW, Australia. Patients who underwent a TKA or THA for OA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 31 publications
2
23
0
2
Order By: Relevance
“…It has also been suggested that ceramic surfaces could be more resistant to biofilm formation and reduce the risk of chronic periprosthetic joint infections. However, this theoretical advantage has not been observed in registry studies [ 18 , 31 ]. The TiN surface is also thought to facilitate interdigitation between the implant and the bone cement [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that ceramic surfaces could be more resistant to biofilm formation and reduce the risk of chronic periprosthetic joint infections. However, this theoretical advantage has not been observed in registry studies [ 18 , 31 ]. The TiN surface is also thought to facilitate interdigitation between the implant and the bone cement [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, at present, our model can only be used for SSI detection in patients undergoing hip replacement. Although the unbalanced nature of our sample required the use of weights to ensure a high negative predictive value, the overall prevalence of hip prosthetic joint infection in the general population (1•3% to 2•2%) 22 is similar to that of our sample, indicating that our model could be used successfully in other centers, although further validation is needed.…”
Section: Discussionmentioning
confidence: 61%
“…The main causes of survival and efficacy for the joint replacement prosthesis include poor force line of the lower extremities, infection, aseptic loosening of the prosthesis, and anterior pain ( 12 ). Among them, prosthetic infection is with an incidence rate of 0.69–2.2% ( 13 , 14 ). Once infection occurs, it requires surgery and long-term use of antibiotics to be treated, and treatment failure is common.…”
Section: Discussionmentioning
confidence: 99%